The estimation of biological tissues trauma under their perforation by one-dimensional implants (AIP conference proceedings, 2015)
The subject of paper is a base stage of positioning of one-dimensional implants (fixing, diagnostic) element, stretching through an aperture in a biotissue. Corresponding mechanical and mathematical model describes implant interaction with biotissues in the conditions of sticking and sliding of contacting surfaces. Theoretical dependences for implant elongation and the maximum value of stress tensor intensity in interfacing volumes of the material are presented, allowing one to calculate the frictional and mechanical characteristics of one-dimensional implant and to estimate the injuring action from biomechanics point of view.